PREPARATION, PHYSICO-CHEMICAL CHARACTERIZATION AND ANTIBACTERIAL PROPERTIES OF CHITOSAN AND CHITOSAN–NISIN MEMBRANES - MATICA, Mariana Adina; AACHMANN, Finn Lillelund; TØNDERVIK, Anne; SLETTA, Håvard; OSTAFE, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Different types of chitosan were used to prepare membranes with enhanced antibacterial properties, via the solvent casting method. Nisin, an antimicrobial peptide, already use in food preservation, was incorporated in chitosan membranes to enhance the bactericidal effect, to obtain a starting material intended for use as wound dressings. The physico-chemical properties of the membranes were monitored and the results showed a good swelling capacity and water vapor transmission rate of the membranes. Optical characterization data showed that chitosan-based membranes could provide ultraviolet light protection while in vitro biodegradability assay demonstrated good stability of the films under enzymatic degradation. Nisin improved significantly the antibacterial effect of the membranes, while the nisin-chitosan membrane-forming solutions had a bactericidal effect against both Gram-positive and Gram-negative bacteria.